Characterization of fungicide sensitivity profiles of Botrytis cinerea populations sampled in Lombardy (Northern Italy) and implications for resistance management. Issue 6 (13th February 2020) - Toffolatti, Silvia L; Russo, Giuseppe; Bezza, Davide; Bianco, Piero A; Massi, Federico; Marcianò, Demetrio; Maddalena, Giuliana
Abstract: BACKGROUND: Resistance to fungicides is one of the aspects that must be considered when planning treatments to achieve an optimal control of grey mold, caused by Botrytis cinerea, in vineyards. In this study, extensive fungicide resistance monitoring was carried out in Northern Italy (Lombardy region) to evaluate several aspects of fungicide resistance (frequency of resistance, effect of field treatments, mechanism of resistance and fitness) on 720 B. cinerea strains isolated from 36 vineyards. RESULTS: Of the characterized strains, 12% were resistant to a single fungicide class (3% to the succinate dehydrogenase inhibitor boscalid, 4% to the anilinopirimidine cyprodinil; 5% to the phenylpirrole fludioxonil; 0.1% to the ketoreductase inhibitor fenhexamid) and 0.8% to two fungicide classes contemporaneously. Resistance was associated with mutations reported in the literature for boscalid (H272Y/R) and fenhexamid (P238S or I232M). Two new mutations in sdh C (A187F) and in sdh D (I189L) could be related to boscalid resistance. Strains resistant to fludioxonil did not show any known mutations. No significant differences were found in the fitness of sensitive and resistant strains. CONCLUSION: Overall, field populations of B. cinerea showed a relatively low frequency of resistance, but the geographical distribution of resistance, genetic mechanisms of resistance and fitness of resistant strains suggest that management of resistance should be implemented, at local and regional levels. Particular attention should be given to the fungicide sprays planned before veraison, since they seem to be associated with a higher frequency of resistant strains in vineyards. © 2020 Society of Chemical Industry Abstract : From the field to the lab and back to the field: fungicide resistance and fitness assessment in Botrytis cinerea populations provides information for an improved resistance management. © 2020 Society of Chemical Industry